Transformational leadership, organizational culture, and employees' commitment: mediation effects chain in the textile industry - Rodrigues, José Pedro (2024)
Issues related to human resource management (HRM) and firm values, such as transformational leadership (TL), organizational culture (OC), motivation, job satisfaction (JS), and employee commitment, have been extensively studied within the business context to understand their impact on firms' efficiency. However, many questions remain regarding the nature of the relationships between these different constructs. This study examines employees' perceptions within the specific context of textile industry firms in Northern Portugal. This industry is particularly crucial to Portuguese economic performance, evidenced by indicators such as employment levels, exports, sales volume, and production.The main objectives of this study are (1) to analyze the perception of employees of northern Portuguese textile firms regarding the influence of TL, OC, motivation, and JS on employees' commitment and (2) to verify the possible mediating effects of JS and motivation in the relationships between TL and commitment, and between OC and commitment. This study was developed using a sample of 235 employees from seven firms in the Portuguese textile sector. A quantitative data analysis methodology was used from a structural equation model, using the IBM Amos software (version 26.0). Based on an innovative conceptual model, ten hypotheses were formulated and tested, drawing upon a prior literature review. It is shown that TL is a direct determinant of OC, motivation, JS, and employees' commitment. TL is also linked indirectly with employees´ commitment through the mediating effects of OC, motivation, and/or JS. Additionally, it was concluded a direct and positive relationship between OC and motivation, and between motivation and commitment. On the contrary, direct relationships between OC and JS, and between JS and commitment have not been confirmed. It was also possible to verify a relationship between OC and employees' commitment, both directly and indirectly, through the mediating effect of motivation. JS was not shown to mediate this relationship. Our study differs and is innovative in several theoretical and managerial features, such as the conceptual model defined, the geographic context, and the industry context covered. Our results are relevant to HRM in the textile industry, highlighting the critical importance for managers to consider their leadership style carefully. Adopting a TL style, coupled with fostering a supportive OC, is essential. This approach can significantly enhance employees' engagement and contribute to the overall success of the firms.